Practical Applications in Asset and Liability Management in Insurance Companies - Candrák, Patrik (2025)
This thesis reviews how an insurance company protects their balance sheet from selected undesired changes. We apply methods to stabilize insurer’s own funds under changeable interest rates. The work outlines the principles of interest rates and bonds, which constitute the greatest portion of a Czech insurer's asset portfolio. Literature is reviewed on duration as a measure of its sensitivity to market rate shifts. Commentary on cash flow modeling is given within a brief section on life insurance theory. We examine the sensitivity of classical insurance products, and their portfolio, to parallel and non-parallel yield curve shifts. Duration of modelled liability cash flows is approximated to compare with a government bond portfolio before and after intervention. While Czech insurers’ options today in asset and liability management remain limited, we give some methods available to control risk exposure.